The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/obr.13384
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of metabolomic studies of childhood obesity: State of the evidence for metabolic determinants and consequences

Abstract: Summary Childhood obesity has become a global epidemic and carries significant long‐term consequences to physical and mental health. Metabolomics, the global profiling of small molecules or metabolites, may reveal the mechanisms of development of childhood obesity and clarify links between obesity and metabolic disease. A systematic review of metabolomic studies of childhood obesity was conducted, following Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines, searching across Scopus, Ovid, Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 77 publications
1
29
0
1
Order By: Relevance
“…Higher levels of tyrosine (an AAA) and leucine (a BCAA) were associated with obesity, SMFQ, and depression symptoms with consistent effects. Both tyrosine and leucine are widely and consistently associated with childhood obesity ( Handakas et al, 2021 ). A recent study in children showed that high tyrosine levels during life are associated with more internalizing behaviors and negative emotions ( Van Vliet et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Higher levels of tyrosine (an AAA) and leucine (a BCAA) were associated with obesity, SMFQ, and depression symptoms with consistent effects. Both tyrosine and leucine are widely and consistently associated with childhood obesity ( Handakas et al, 2021 ). A recent study in children showed that high tyrosine levels during life are associated with more internalizing behaviors and negative emotions ( Van Vliet et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies showed that gut microbiota play a causal role in the development of features of depression ( Kelly et al, 2016 ) and anxiety ( De Palma et al, 2017 ), supporting further evidence that there is a modulation of neurotransmission that is likely a route of communication along the gut-brain axis. Plasma AAAs, which are directly modulated by the gut microbiota ( Handakas et al, 2021 ) could therefore influence later propensity for mental health disorders through metabolic processes of gut and brain interaction. BCAAs, including leucine, play an important role in the activation of the mammalian target of rapamycin (mTor) pathway–a pathway involved in the control of cell growth and proliferation–and has been associated with a short-term decrease in depressive symptoms ( Baranyi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, as bisphenol A is poorly soluble in water, the presence in blood can result from high levels in drinking water [92]. Finally, it should be pointed out that a number of different factors need to be considered when undertaking metabolomic studies, including diet [110] and comorbidities [111][112][113][114][115][116][117][118][119]. In this regard, obesity [111,112], chronic obstructive pulmonary disease [113][114][115], kidney disease [116], diabetes [117,118], and cardiovascular disease [94] have all been reported to have a major impact on the metabolome that can confound metabolomic studies in cancer, and thus, their influence cannot be underestimated.…”
Section: Effect Of Underlying Diseases or Non-related Metabolitesmentioning
confidence: 99%